Clinical Considerations in the Selection of Preexposure Prophylaxis for HIV Prevention in Canada - David C. Knox; Robert Pilarski; Harvinder S. Dhunna; Amit Kaushal; Jonathan D. Adachi (Canadian Journal of Infectious Diseases and Medical Microbiology)
According to the Public Health Agency of Canada, approximately 62,050 people were living with HIV in Canada in 2018, and of those, 13% were undiagnosed. Currently, no single strategy provides complete protection or is universally effective across all demographic groups at risk for HIV. However, HIV preexposure prophylaxis (PrEP) is the newest HIV prevention strategy that shows promise. To date, two products have received an indication for PrEP by Health Canada: emtricitabine/tenofovir disoproxil fumarate (Truvada®; FTC/TDF) and emtricitabine/tenofovir alafenamide (Descovy®; FTC/TAF). Despite the high efficacy of these PrEP intervention methods, access to PrEP in Canada remains low. Identifying and addressing barriers to PrEP access, especially in high-risk groups, are necessary to reduce HIV transmission in Canada. While guidelines published by the Center for Disease Control and Prevention (CDC) include FTC/TAF information, the efficacy of FTC/TAF for PrEP has not yet been considered in Canada’s clinical practice guidelines. Thus, the current paper reviews data regarding the use of FTC/TDF and FTC/TAF for PrEP, which may be useful for Canadian healthcare providers when counseling and implementing HIV prevention methods. The authors highlight these data in relation to various at-risk populations and review ongoing clinical trials investigating novel PrEP agents. Overall, FTC/TDF PrEP is effective for many populations, including men who have sex with men, transgender women, heterosexuals with partners living with HIV, and people who use drugs. While there is fewer data reported on the efficacy of FTC/TAF to date, recent clinical trials have demonstrated noninferiority of FTC/TAF in comparison to FTC/TDF. Notably, as studies have shown that FTC/TAF maintains renal function and bone mineral density to a greater extent than FTC/TDF, FTC/TAF may be a safer option for patients experiencing renal and/or bone dysfunction, for those at risk of renal and bone complications, and for those who develop FTC/TDF-related adverse events.